Water Quality Index Performance for River Pollution Control Based on Better Ecological Point of View (A Case Study in Code, Winongo, Gadjah Wong Streams) - Sri Puji Saraswati; Mochammad Venly Ardion; Yul Hendro Widodo; Suwarno Hadisusanto (Journal of the Civil Engineering Forum, 2019)
The quality of river water quality monitoring data sometimes can be inaccurate. Evaluation of the effectiveness of water pollution control programs needs good quality data to calculate the Water Quality Index (WQI) with the aim to meet the requirement to protect biodiversity and maintain various water functions. Thirty-five water quality variables from Code, Gadjah Wong, and Winongo rivers were taken as data, conducted by Environmental Agency of Yogyakarta in 2004 – 2015. There were only 19 out of 35 water quality variables having good data after improvement of monitoring data, transformation/standardization and analysis of the significant water quality variables with PCA (Principle Component Analysis) and Factor Analysis (FA). WQIs formula in the three rivers used the same 5 significant variables i.e. EC, DO, COD, NH3N, Total Coliform, and "weighted sum index” as the sub-index aggregation technique, with different sub-index coefficients. Winongo River had the best water quality and Gajah Wong River was the worst. According to the relationship of river water discharge and WQIs index, large discharge during rainy seasons does not always decrease the level of pollution, but it tends to increase the WQIs. More effective ways to improve the stream water quality during dry seasons should further be investigated.